NEEDS ANALYSIS OF GAMIFICATION MODELS IN THE DIGESTIVE SYSTEM LESSON TO IMPROVE STUDENTS' CRITICAL THINKING SKILLS AND SCIENCE PROCESS SKILL - Maulidia, Rachmani; Jaenudin, Dadang; Chemistry, Valerie Indiana (JOURNAL OF SCIENCE EDUCATION AND PRACTICE, 2024)
The human digestive system is one of the essential Biology learning materials so that in understanding it requires high-level skills and in-depth thinking. In general, current learning still often uses conventional learning methods and media so that it is considered less effective in improving students' critical thinking skills and science process skills. Gamification is considered as one of the innovative learning media that can be a solution to improve high-level skills because gamification involves students actively and can increase student motivation in learning Biology This study aims to analyze the needs of gamification learning media for MTS Al-Inayah Bogor schools on human digestive system material which is designed in such a way as to improve students' science process skills and critical thinking skills. This research uses the development research model (R&D) with the ADDIE approach, this research focuses on the analysis stage. The purpose of this study was to analyze the needs of gamification media on human digestive system material to improve students' critical thinking skills and science process skills. Data collection techniques use purpose sampling techniques using student needs instruments using a Likert scale (5 points) through a survey of 72 students in class VIII MTS and 10 Biology teachers. While qualitative data was obtained through interviews with 10 teachers. The results of this study show 91% of classroom learning still uses conventional methods. Learning media that uses game elements is only about 9%, but respondents stated that this media is not enough to improve critical thinking skills. Only 8% have just used gamification, especially in human digestive system material. About 82% stated that they really need gamification learning media to improve students' critical thinking skills and science process skills. This research can be a strong basis for developing gamification media according to the needs of science learning in schools.